Python object-oriented programming : build robust and maintainable object-oriented Python applications and libraries - Lott, Steven F.; Phillips, Dusty (Birhinghman : Packt Publishing, 2021)
Python objected-oriented programming, fourth edition, dives deep into the various aspects of OOP, Python as an OOP language, common and advanced design patterns, and hands-on data manipulation and testing of more complex OOP systems. There concepts are consolidated by open-ended exercises, as well as a real- world case study at the end of every chapter, newly written for this edition. All example code is now compatible with Python 3.9+ syntax and has been updated with type hints for ease of learning.
Chapter 1. Object-oriented design.--Chapter 2. Objects in Python.--Chapter 3. When objects are alike.--Chapter 4. Expecting the unexpected.--Chapter 5. When to use object-oriented programming.--Chapter 7. Python data structures.--Chapter 8. The intersection of object-oriented and functional programming.--Chapter 9. Strings, serialization, and file paths.--Chapter 10. The iterator pattern.--Chapter 11. Common design patterns.--Chapter 12. Advanced design patterns.--Chapter 13. Testing object-oriented programs.--Chapter 14. Concurrency
Includes index.
Keywords: PYTHON; OBJECT-ORIENTED PROGRAMMING; APPLICATION SOFTWARE -- DEVELOPMENT; SOFTWARE MAINTENANCE; SOFTWARE DESIGN